Costs and cost‐effectiveness of the meeting centres support programme for people living with dementia and carers in Italy, Poland and the UK: The MEETINGDEM study. (27th January 2021) - Henderson, Catherine; Rehill, Amritpal; Brooker, Dawn; Evans, Simon C.; Evans, Shirley B.; Bray, Jennifer; Saibene, Francesca Lea; Scorolli, Claudia; Szcześniak, Dorota; d'Arma, Alessia; Lion, Katarzyna; Atkinson, Teresa; et al.
Abstract: We examined the costs and cost‐effectiveness of the Meeting Centre Support Programme (MCSP) implemented and piloted in the UK, Poland and Italy, replicating the Dutch Meeting Centre model. Dutch Meeting Centres combine day services for people with dementia with carer support. Data were collected over 2015–2016 from MCSP and usual care (UC) participants (people with dementia‐carer dyads) at baseline and 6 months. We examined participants' health and social care (HSC), and societal costs, including Meeting Centre (MC) attendances. Costs and outcomes in MCSP and UC groups were compared. Primary outcomes: Persons with dementia: quality‐adjusted life years (EQ‐5D‐5L‐derived); QOL‐AD. DQoL was examined as a secondary outcome. Carers: Short Sense of Competence Questionnaire (SSCQ). Incremental cost‐effectiveness ratios (ICER) and cost‐effectiveness acceptability curves were obtained by bootstrapping outcome and cost regression estimates. Eighty‐three MCSP and 69 UC dyads were analysed. The 6‐month cost of providing MCSP was €4, 703; participants with dementia attended MC a mean of 45 times and carers 15 times. Including intervention costs, adjusted 6‐month HSC costs were €5, 941higher in MCSP than in UC. From the HSC perspective: in terms of QALY, the probability of cost‐effectiveness was zero over willingness‐to‐pay (WTP) ranging from €0 to €350, 000. On QOL‐AD, the probability of cost‐effectiveness of MCSP was 50% at WTP of €5, 000 for a one‐point increase. A one‐point gain in the DQoL positive affect subscale had a probability of cost‐effectiveness of 99% at WTP over €8, 000. On SSCQ, no significant difference was found between MCSP and UC. Evidence for cost‐effectiveness of MCSP was mixed but suggests that it may be cost‐effective in relation to gains in dementia‐specific quality of life measures. MCs offer effective tailored post‐diagnostic support services to both people with dementia and carers in a context where few evidence‐based alternatives to formal home‐based social services may be available.